(untitled) (Revista de Educação Pública, 2012)
O texto apresenta resultados de pesquisa realizada entre 2005 e 2007, com mães de crianças que frequentam uma escola pública do Estado do Rio de Janeiro. Objetiva analisar expectativas de socialização na escola considerando estratégias instrumentais e identitárias. As análises se apoiaram em Pierre Bourdieu, Daniel Thin e Agnès Van Zanten. Foram realizadas entrevistas individuais com seis mães. Para três mães, a escola deve ocupar-se, principalmente do ensino. As demais, que vivem em favelas próximas à escola, revelaram expectativas modestas de socialização na escola. Todas, no entanto, esperam que a escola garanta a guarda das crianças durante o horário escolar. Expectations of socialization in school among mothers Abstract The text presents the results of a research carried out between 2005 and 2007 with children´s mothers attending a public school in the State of Rio de Janeiro. It´s foccussed on the analysis of expectations of socialization in schools considering instrumental strategies and identities. Analysis were based, specially, on Pierre Bourdieu, Daniel Thin and Agnes Van Zanten. Individual interviews took place with six mothers who showed differences in relation to their expectations of school as a socializing place. Three of them fear the experiences of socialization in school. For them, school role should be primarily learning. The others, who live in a slum near the school, show little expecttions of such socialization. Linking the two groups there is the general expection that the school should look after the children, guaranting their safety, during school period. Keywords: Socialization in school. Family and school. Education and poor social layers.